Occupational exposure assessment to particles with task-based approach - Viegas, Susana (2016)
Occupational exposure assessment can be a challenge due to several factors being the most important the costs associate and the result's dependence from the conditions at the time of sampling. Conducting a task-based exposure assessment allow defining better control measures to eliminate or reduce exposure since more easily identifies the task with higher exposure. A research study was developed to show the importance of task-based exposure assessment in four different settings (bakery, horsemanship, waste sorting and cork industry). Measurements were performed using a portable direct-reading hand-held equipment and were conducted near the workers nose during tasks performance. For each task were done measurements of approximately 5 minutes. It was possible to detect the task in each setting that was responsible for higher particles exposure allowing the priority definition regarding investments in preventive and protection measures.